Palaeobotanical records associated with the first dinosaur defined in Spain: Palynostratigraphy, taxonomy and palaeoenvironmental remarks. (October 2018) - Santos, Artai A.; Villanueva-Amadoz, Uxue; Royo-Torres, Rafael; Sender, Luis Miguel; Cobos, Alberto; Alcalá, Luis; Diez, José B.
Abstract: In this paper, we present the study of the palaeobotanical record from Las Zabacheras 1 (palynoflora) and Las Zabacheras 3 (macroflora) fossil sites located in the deltaic sedimentological complex Villar del Arzobispo Formation (Galve, Teruel, northeastern of Spain). Las Zabacheras 1 is the type locality of the first dinosaur defined in Spain (the sauropod Aragosaurus ischiaticus ). In this site a sporomorph assemblage was recovered and it was mainly composed of the genera Exesipollenites and Spheripollenites, with an abundance of the pteridophyte spore genera Concavissimisporites, Impardecispora and Trilobosporites from the site Las Zabacheras 1, indicating a Berriasian–early Valanginian (Early Cretaceous) age. From Las Zabacheras 3, a macro-palaeobotanical assemblage was recorded including different morphotypes of pteridophytes assigned to the genera Cladophlebis, cf. Todites, and cf. Eboracia . These data alongside with charophytes and regional stratigraphic information, more likely suggests an early Berriasian age for the stratigraphic section of the dinosaur Aragosaurus ischiaticus . This work aims to contribute the knowledge of both the palaeoflora and palaeoenvironments around the Jurassic-Cretaceous boundary and the beginning of the Early Cretaceous in the westernmost coast of the Tethys Ocean.